Desempenho de pontas de pulverização quanto a indução de ar nas gotas - Faggion, Francisco [UNESP]; Antuniassi, Ulisses Rocha [UNESP] (EIA Energy in Agriculture, 2010)
An efficient application of agrochemicals depends, among other factors, on the type of nozzles used. Several types of nozzles are available on the market. The air induction nozzles generate droplets with air in their interior, which alters both the behaviour and the spectrum of the droplets. The objective of this research was to assess the performance of air induction nozzles regarding the amount of air induced, in function of the nozzle output and the work pressure. A funnel was built in order to capture the droplets with air; those droplets were captured in order to find out the volume of the mixture and the weight of the mass of the liquid. The following agricultural air induction nozzles were evaluated: AI 110015, AI 11002, AI 11003 and AI 11004. The solution spread was composed of water with 0.1% v/v of a nonionic surfactant based on nonylphenoxy polyethyoxyethanol, sprayed at working pressures of 200, 250, 300, 350, and 400 kPa. The air induction nozzles induced an average of 21,51% of air on the droplets. The variation of the working pressure had influence on the percentage of air included and the nozzles where similar to each other regarding the induction of air maintaining constant the working pressure.

Uma pulverização eficiente é dependente, dentre outros fatores, da ponta de pulverização utilizada. Existem vários tipos de pontas de pulverização disponíveis no mercado, sendo que as pontas com indução de ar geram gotas com ar em seu interior, o que altera o comportamento e a estrutura do espectro de gotas. O objetivo deste trabalho foi avaliar o desempenho de pontas com indução de ar quanto a quantidade de ar induzido em função da vazão da ponta e da pressão de trabalho. Para tanto foi construído um funil para capturar as gotas pulverizadas a partir de pontas com indução de ar, coletando-se o líquido para determinação de sua densidade, com consequente estimativa da quantidade de ar induzido. As pontas avaliadas foram as seguintes: AI 110015, AI 11002, AI 11003 e AI 11004. A calda utilizada foi composta da mistura de água com surfactante não iônico a base de nonil fenoxi poli (etilenoxi) etanol, na concentração de 0,1% v/v, aplicado nas pressões de 200, 250, 300, 350 e 400 kPa. Os resultados mostraram que as pontas estudadas induziram em média 21,51% de ar nas gotas nas diferentes pressões avaliadas, sendo que a variação da pressão de trabalho alterou a porcentagem de ar incluído às gotas. Para uma mesma pressão, as pontas foram semelhantes entre si quanto a indução de ar.
Performance of air induction nozzles regarding the amount of air induced on the droplets
Keywords: Application technology; Pressure; Air inclusion; Tecnologia de aplicação; Pressão; Inclusão de ar